Pembentukan Karakter Siswa Melalui Permainan Tradisional Gatrik - Asep Awaludin; Achmad Hufad; Suroso Multi Leksono (Peneliti.net, 2022)
Every teacher has knowledge and understanding of character education, but not all teachers have mastered the methods in shaping children's character. The reason was the weakness of the teacher's creativity in shaping the child's character. The traditional gatrik game can actually be used as a teacher as a medium in shaping children's character. This has been done by the teacher at SDN Jangkar Cilegon. This study aims to describe the efforts to shape children's character with the traditional gatrik game at SDN Jangkar. The study was conducted with a phenomenological type of research with the subjects of the principal, teachers, and students of the Jangkar Elementary School. Data were collected using interviews, observations, and document studies, then data analysis was carried out in three stages, namely data reduction, data presentation, and verification. The results of the study describe that efforts to shape children's character with traditional gatrik games at SDN Jangkar are carried out in three stages. First, introduce the values ​​of kindness through traditional games. Second, to encourage children to realize good values ​​when playing with traditional games. Third, provide instructions for children to display good behavior when playing with traditional gatrik games. In the implementation of the three stages, the teacher not only accompanies and teaches how to play but also becomes a role model for children to do good things when playing with traditional gatrik games.